Financial Statement Fraud Detection with The Pentagon Fraud Theory Perspective: Audit Committee Effectiveness as a Moderating Variable - Laksito, Herry; Purwiyanti, Deviana Wahyu (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2026)
This study aims to examine the fraud factors in the fraud pentagon theory on the potential for financial statement fraud in financial sector companies listed on the Indonesia Stock Exchange (IDX) during 2019–2024. The independent variables include financial targets, ineffective supervision, changes in company auditors, changes in directors, and CEO duality. The dependent variable is the potential for financial statement fraud, measured using the Beneish M-Score formula. The study also includes a moderating variable, namely the effectiveness of the audit committee, measured by the expertise of audit committee members and the frequency of audit committee meetings. The study analyzes 491 observations from financial sector companies using logistic regression and Moderated Regression Analysis (MRA). Results show that out of 15 hypotheses, 9 are supported. Independent variables that significantly influence the potential for financial statement fraud are financial targets, ineffective supervision, changes in auditors, and changes in directors. The moderating variables successfully moderate the relationship between pressure, rationalization, and competence. The study highlights that high public expectations for companies to generate substantial profits often drive financial reporting fraud. In addition to pressure, other conditions can also motivate fraudulent behavior. This research is important as it emphasizes the role of audit committee effectiveness in minimizing the potential for fraud and provides an empirical perspective on the application of the fraud pentagon theory in the Indonesian financial sector.